The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jocn.13947
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Chinese culture on family caregivers of stroke survivors: A qualitative study

Abstract: Aims and objectives: To explore and describe the caregiving experiences of Chinese stroke caregivers.Background: Previous research has indicated that culture can have a significant impact on the stroke caregiving experience. Moreover, scant research exists on stroke caregivers' experience within the Chinese culture.Design: A qualitative descriptive design was used.Methods: In-depth, semistructured interviews were conducted with 25 family caregivers of stroke survivors. The interviews were audiotaped, transcrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 47 publications
7
120
0
2
Order By: Relevance
“…Our findings indicate various levels and forms of family involvement in the process of body donation: some registered donors did not communicate with family members about their body donation at all, but some bereaved family members put a lot of effort into implementing the body donation decisions made by their deceased family members. Despite the variance, part of our findings suggest that their intention is still on valuing the importance of family relationships, which is consistent with the literature highlighting the importance of family obligations and self‐sacrifice for family members in the Chinese cultures (Qiu, Sit, & Koo, ; Shek, ). For example, in order to avoid conflicts with family members, registered donors did not disclose their decisions to their elderly parents, who are likely to object to their decisions.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings indicate various levels and forms of family involvement in the process of body donation: some registered donors did not communicate with family members about their body donation at all, but some bereaved family members put a lot of effort into implementing the body donation decisions made by their deceased family members. Despite the variance, part of our findings suggest that their intention is still on valuing the importance of family relationships, which is consistent with the literature highlighting the importance of family obligations and self‐sacrifice for family members in the Chinese cultures (Qiu, Sit, & Koo, ; Shek, ). For example, in order to avoid conflicts with family members, registered donors did not disclose their decisions to their elderly parents, who are likely to object to their decisions.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with findings from Hayashi et al (), who identified that 67.4% of caregivers of stroke survivors were women. In Japan and China, Kaneko and Kanekawa () and Qiu, Sit, and Koo () found that 74.5% and 76% of caregivers of stroke survivors were females. This could be explained by the social structure in many Asian countries, where the social and cultural expectation of caring roles require the women to be responsible for ill family members (Hoang, ; Qiu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients' crucial need encompassed of feelings of being independent to lead a quality of life, reducing the severity and prevent recurrent stroke [13][14][15][16]. To be able to achieve these aim, the patient would utmostly require confidence and self-efficacy.…”
Section: Methodsmentioning
confidence: 99%